Implementation of Job Analysis Policy in Employee Placement at the Regional Secretariat of South Buton Regency - Asmiddin Asmiddin; ⁠La Didi; Melita Zahabu (Sean Institute, 2025)
The purpose of this study is to describe the implementation of job analysis policy in employee placement at the Regional Secretariat of South Buton Regency using Charles O. Jones's policy implementation theory, which includes three main dimensions: organization, interpretation, and application. The research method used is a descriptive qualitative approach. Data were collected through observation, interviews, literature studies, and documentation. Data sources were obtained from informants through direct observation and interviews, and documents obtained in the form of regulations. Data processing was analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and verification. The results show that in the organizational dimension, job analysis implementation is still carried out ad hoc without a permanent implementation team or standardized SOPs. Limited human resources, uneven technical training, and the use of manual methods without an integrated information system are the main obstacles. In the interpretation dimension, the policy has been described in normative documents such as Regent Regulations and job maps, but has not been equipped with detailed local technical SOPs. Directions and training for implementers have also not been carried out systematically, resulting in differences in understanding between work units. In the application dimension, job analysis results have not yet been fully utilized as a strategic basis for employee placement. Employee placement is based more on immediate needs and the considerations of immediate superiors, without a structured and ongoing job evaluation cycle.